Comparing Different Methods to Estimate the Combined Mesiodistal Widths of Maxillary and Mandibular Incisors - Mohammed Nahidh (Galenos Yayinevi, 2018)
Objective:This study aimed to develop regression equations to predict the combined mesiodistal widths of maxillary and mandibular incisors from each other and compare them with other methods.Methods:One hundred pairs of study models from 100 Iraqi subjects with normal occlusion were used in this study. The individualized mesiodistal widths of maxillary and mandibular incisors were measured using electronic digital calipers. The combined mesiodistal widths of maxillary and mandibular incisors were calculated according to Tonn's and Abhi's formulas and from regression equations to be compared with the actual one.Results:Both sums of the maxillary and mandibular incisors were significantly correlated. There were significantly high differences between the actual and calculated sum widths, and also between the calculated and predicted ones. On the other hand, a non-significant difference was obtained between the actual and predicted sum widths of maxillary and mandibular incisors.Conclusion:Tonn's and Abhi's methods are not reliable methods to calculate the sum widths of maxillary and mandibular incisors. New regression equations are developed to predict the sum widths of maxillary and mandibular incisors from each other.